Analysis of subclinical synovitis detected by ultrasonography and low-field magnetic resonance imaging in patients with rheumatoid arthritis. Issue 1 (January 2014) - Ogishima, Hiroshi; Tsuboi, Hiroto; Umeda, Naoto; Horikoshi, Masanobu; Kondo, Yuya; Sugihara, Makoto; Suzuki, Takeshi; Matsumoto, Isao; Sumida, Takayuki
Abstract: Objective To assess the utilities of ultrasonography (US) and low-field magnetic resonance imaging (compacTscan, cMRI) in the diagnosis of subclinical synovitis of hand joints of patients with rheumatoid arthritis (RA). Methods A total of 1, 540 joints of 77 RA patients were examined clinically, using US, using cMRI, and the baseline X-ray examination was performed. Clinical synovitis was defined as joint tenderness or swelling. Subclinical synovitis was diagnosed by US and by cMRI. The incidence of bone erosion and joint space narrowing was assessed by X-ray examination performed at approximately 40 weeks of follow-up. Results Of the hand joints examined, 294 (19.1 %) were diagnosed with clinical synovitis, and 218 joints (14.1 %) were diagnosed with subclinical synovitis. The remaining 1, 028 joints (66.8 %) were synovitis-free on clinical examination and imaging. For the diagnosis of subclinical synovitis, cMRI (11.4 %) was significantly more sensitive than power Doppler signals detected by US (US-PD; 6.8 %) ( P < 0.01), and the combination of US-PD and cMRI was more useful (14.1 %) than US-PD or cMRI alone ( P < 0.05). Follow-up X-ray examination of 600 joints showed a significantly higher incidence of bone erosion in joints with subclinical synovitis than in synovitis-free joints ( P < 0.05). Conclusion US-PD and cMRI are useful for detecting subclinical synovitis in patients with RA. Subclinical synovitis of the small joints of the hand can progress to bone destruction.